Resolving Conflicts between Agriculture and the Natural Environment - Tanentzap, Andrew J.; Lamb, Anthony; Walker, Susan; Farmer, Andrew (PLOS Biology, 2015)
Agriculture dominates the planet but has many environmental costs that will escalate with global food demand. This Essay outlines a vision for a more sustainable future.